Simulation Model on Movement of Goods in Sea Freight for Small and Medium Enterprise - Zirawani Baharum; Muhammad Hanif; Muhammad Imran Qureshi; Syazwa Nabila Mohd Raidzuan; Hairulnizam Mahdin (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Sea transportation is one of the major transportation in the scope of transport industry and plays important role towards the growth of performance in the industry that involves the movement of good (MOG). With the crucial operations, it is also essential to concern about the employee’s welfare, such as long working hours that occurred due to non-systematic procedure for the MOG. The long working hours been potentitially impact to the psychological factors of works stress and physical and health effects. Therefore, this research is important to be studied in order to develop the simulation model on MOG in sea freight for small and medium-sized enterprises (SMEs), effectively and efficiency. Initially, this research is startup by defining all existed activities with the duration as required. Subsequently, the business model of MOG in sea freight is developed according to the case study in order to develop the simulation model. This research is give a guide for future research towards providing a well-computer-based by applying the decision support system, especially to manage and control the movement of goods in sea freight.